Relationship Of Pregnant Mother Satisfaction In Antenatal Care Services With Motivation To Do Antenatal Care - Mail, Erfiani; Yuliani, Farida; Wari, Fitria Edni (Universitas Islam Lamongan, 2023)
Quality of health services provided by the government still has not or does not meet the expectations of patients and the public. This study aims to determine the relationship between the satisfaction of pregnant women at antenatal care with the motivation to do antenatal care. This research is an analytical study, which uses cross sectional design. The population in this study of pregnant women who do antenatal care in rural Puskesmas Gayaman Kabupaten Mojokerto is 58 people. The sample size in this study were 30 respondents. The sampling technique with a non-probability sampling techniques with the type of accidental sampling. Data collection techniques using primary data in the form of questionnaires and secondary data obtained from the KMS pregnant women. Techniques used in data analysis is Spearman Rank correlation. The study was conducted in Puskesmas Gayaman Kabupaten Mojokerto village on June 15 to June 29, 2022. The results of this study showed that pregnant women who feel very satisfied that as many as 23 respondents (76.7%), and pregnant women who have good motives as much as 26 respondents (86.7%). From the analysis of the data by Spearman Rank test, the result shows that the calculated Ï Ï table 0.5468 and 0.364, the price can be seen that Ï greater than Ï count table that means there is a correlation between the satisfaction of pregnant women at antenatal care with the motivation to do antenatal care. Â Â Â Â Â Â Â Â Â Satisfaction of pregnant women in antenatal care of pregnant women affect the motivation to perform antenatal care. A good midwife services, facilities, friendly attitude of midwives, midwives skills in responding quickly to face the problems of patients so that respondents are motivated to come back. The motivation is called extrinsic motivation, namely the stimulation comes from outside or other people. Conclusions from this study are doing antenatal care satisfaction related to the motivation of doing antenatal care. Suggestions for health services in accordance with the result expected service quality can be maintained and further enhanced.